Optimum-Path Forest: Theory, Algorithms, and Applications - Xavier Falcao, Alexandre; Papa, João Paulo (Elsevier Science & Technology, 2022)
The Optimum-Path Forest (OPF) classifier was first published in 2008 in its supervised and unsupervised versions with applications in medicine and image classification.Since then, it has expanded to a variety of other applications such as remote sensing, electrical and petroleum engineering, and biology.